2006
DOI: 10.1016/j.lisr.2006.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Are virtual reference services color blind?

Abstract: This study reports an experiment that examines whether librarians provide equitable virtual reference services to diverse user groups. The relative absence of social cues in the virtual environment may mean greater equality of services though at the same time greater inequalities may arise as librarians can become less self-aware online. Findings indicate that the quality of service librarians provide to African Americans and Arabs is lower than the quality of service they provide to Caucasian, Hispanic, Asian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 18 publications
1
41
3
Order By: Relevance
“…Some authors argue that librarians' interactions with users are comparable to the doctor-patient relationship (e.g., White, 1985), while others advocate the use of counseling techniques (as discussed in Radford, 1999). This approach to the reference encounter has driven the formulation and publication of professional guidelines for librarians (e.g., Ross, Nilsen, & Dewdney, 2002;Reference and User Services Association [RUSA], 2004); these guidelines are then used for the evaluation of reference transactions (Kwon, 2006;Shachaf & Horowitz, 2006Walter & Mediavilla, 2005;Ward, 2003;Zhuo, Love, Norwood, & Massia, 2006). In social reference, task processes would be valuable predictors of the outputs as much as they have been for the library reference outputs.…”
Section: Task Processesmentioning
confidence: 99%
“…Some authors argue that librarians' interactions with users are comparable to the doctor-patient relationship (e.g., White, 1985), while others advocate the use of counseling techniques (as discussed in Radford, 1999). This approach to the reference encounter has driven the formulation and publication of professional guidelines for librarians (e.g., Ross, Nilsen, & Dewdney, 2002;Reference and User Services Association [RUSA], 2004); these guidelines are then used for the evaluation of reference transactions (Kwon, 2006;Shachaf & Horowitz, 2006Walter & Mediavilla, 2005;Ward, 2003;Zhuo, Love, Norwood, & Massia, 2006). In social reference, task processes would be valuable predictors of the outputs as much as they have been for the library reference outputs.…”
Section: Task Processesmentioning
confidence: 99%
“…Kwon (2007), for example, reports different levels of question answering effectiveness by request type in collaborative virtual reference services. Finally, Shachaf and Horowitz (2006) report different levels of service quality to Arabs and African Americans compared to Caucasian users. Using the knowledge that was gained from prior research about variations in the level of service quality by request type, institution, and user name the expectations in this study are that variations in adherence to professional guidelines may be found.…”
Section: Evaluation Of Virtual and Traditional Reference Servicesmentioning
confidence: 99%
“…Empirical studies of virtual reference transactions report variations in the level of effectiveness by question type (Kwon, 2007), by institution (Stacy-Bates, 2003), and by user name (Shachaf & Horowitz, 2006). For example, Stacy-Bates (2003) reports variations among ARL institutions in the provisions of virtual reference services.…”
Section: Evaluation Of Virtual and Traditional Reference Servicesmentioning
confidence: 99%
See 2 more Smart Citations